The Globalization of Knowledge in the Iberian Colonial World - Helge Wendt (ed.) (Proceedings 10: Max Planck Research Library for the History and Development of Knowledge, 2016)
This volume investigates processes of knowledge formation in the Iberian colonies by attempting to understand the Spanish and Portuguese contribution to the European scientific tradition, and by tracing the origins and history of this knowledge to find out how it was gained. The studies in this volume reconsider our understanding of what scientific knowledge is and introduce a variety of scientific cultures of European and non-European origin. They examine the mixing processes of scientific cultures and the role these cultures played in the colonial situation at the intersection of non-human processes and human action. The volume brings together contributions in the history of botany, art, materia medica, translation in the religious sphere of colonial missions as well as mining as a scientific, juridical and industrial endeavor.